Sequentially optimizing carbon nanotubes framework towards flexible and compact capacitive energy storage. Issue 40 (26th September 2022) - Yin, Qing; Ye, Mingyu; Jia, Hongbing; Arcanjo de Araújo Melo, Antonio Francisco; Ji, Qingmin
Abstract : The favorable interfacial π–π interactions between a carbon nanotubes (CNTs) network and an aramid nanofibers (ANFs) film make it possible to assemble a porous yet robust CNTs-based electrode with a double-layer architecture. Abstract : A porous carbon nanotubes (CNTs) framework has long been considered as one promising candidate for supercapacitors, but its flexible applications have been restricted by the extremely low mechanical performance. More importantly, efficiently integrating stack capacitance and mechanical stability has not yet been fully realized for CNTs-based supercapacitors. Herein, a practically feasible CNTs-based electrode is designed by introducing an aramid nanofibers (ANFs) film. A pre-constructed double-layer CNTs@ANFs architecture, the first example of loading an intact CNTs porous coating on a synthetic polymer substrate at the mg cm −2 level, realizes impressive strengthening and toughing of the CNTs framework (11.5- and 78.6-times improvement in strength and toughness, respectively). Benefiting from robust mechanical properties, the double-layer film achieves compact capacitance delivery (118.6 F cm −3 ) by in situ tailoring the surface chemistry of CNTs and subsequently coupling high-loading polyaniline (PANI) through an electrochemical means. Furthermore, a flexible solid-state supercapacitor based on the PANI@CNTs@ANFs film electrode delivers an ultrahigh volumetric capacitance of 9.4 F cm −3 with a stack energy density of 0.78 mW h cm −3 . The prominent structure–function relationship validated in this work represents a substantial breakthrough for optimizing the porous CNTs framework towards flexible and compact capacitive energy storage, which is of both fundamental and technical importance for advanced structural energy and power systems.